2019
DOI: 10.1289/ehp4434
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to PM2.5 and Cardiac Vagal Tone during Infancy: Findings from a Multiethnic Birth Cohort

Abstract: Background:The autonomic nervous system plays a key role in maintaining homeostasis and responding to external stimuli. In adults, exposure to fine particulate matter (PM2.5) has been associated with reduced heart rate variability (HRV), an indicator of cardiac autonomic control.Objectives:Our goal was to investigate the associations of exposure to fine particulate matter (PM2.5) with HRV as an indicator of cardiac autonomic control during early development.Methods:We studied 237 maternal–infant pairs in a Bos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…Emerging evidence suggests that prenatal and postnatal PM 2.5 exposure can result in heart failure later in life [84]. A study conducted by Gorr et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that prenatal and postnatal PM 2.5 exposure can result in heart failure later in life [84]. A study conducted by Gorr et al.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure. Emerging evidence suggests that prenatal and postnatal PM 2.5 exposure can result in heart failure later in life [84]. A study conducted by Gorr et al in 2014 exposed female mice to PM 2.5 during pregnancy and found an association with reduced left ventricular fractional shortening with greater ventricular systolic diameter, reduced ejection fraction, and other indicators of cardiac dysfunction when compared to control mice during a postnatal time [85].…”
Section: Ischemic Heart Disease and Myocardial Infarctionmentioning
confidence: 99%
“…PM is one of the crucial air pollutants and found to cause a wide range of health effects in human ( Manojkumar and Srimuruganandam, 2021 ). Epidemiological studies have revealed a strong association between PM and diseases involving multiple organ system ( Cowell et al, 2019 ; Gu et al, 2020 ). For instance, the link between PM and the aggravation of respiratory illness such as, allergy and asthma has been well documented ( Chowdhury et al, 2018 ).…”
Section: Atmospheric Particulate Mattermentioning
confidence: 99%
“…Besides, International Agency for Research on Cancer (IARC) has reported that PM in outdoor air pollution is a human carcinogen ( IARC, 2016 , Sun et al, 2018 ). Short term exposure to PM was significantly associated with acute cardiovascular risks like, myocardial infarction, arrhythmias, hypertension and metabolic syndrome ( Chen et al, 2020a ; Cowell et al, 2019 ). Furthermore, PM could also accelerate the risk of neurological effects, including Alzheimer’s disease and dementia ( Younan et al, 2020 ).…”
Section: Atmospheric Particulate Mattermentioning
confidence: 99%
See 1 more Smart Citation